Financial Management Practices and Financial Performance of Micro Finance Institutions. A Case Study of Lyamujungu SACCO Kabale District. - Komuhangi, Jacenta (Kabale University, 2023)
The study was sought to establish the relationship between financial management practices and financial performance of microfinance institutions in Uganda. This study was anchored on two theories which included; Stewardship Theory and Stakeholder theory. The determinants of financial performance included return on assets, profitability and loan portfolio. The study relied on cross-sectional survey design as its research design, data was collected using questionnaire. Data was analyzed using SPSS 20.0 and other descriptive statistics. Descriptive statistical tools included frequencies, percentages, means and standard deviations. Inferential statistics included Pearson’s Product Moment Correlation and multiple regression analysis. A sample of 109 respondents was selected using simple random and purposive sampling. The primary method of data collection was the self-administered questionnaire while correlation constituted data analysis. The findings indicate that internal control systems, cash flow management, and working capital management significantly affect financial performance of microfinance institutions. Regarding the effect of internal control on financial performance, the study findings revealed that Pearson Rank Correlation (R = .794**), sig. value p<0.01 and sample size (n=109). Basing on the above results, the study reveals that there is a statistically strong positive significant relationship between internal control systems and Financial Performance Regarding the correlation between cash flow management and financial performance, the study findings revealed that Pearson Rank correlation (r=-.753**), sig. value p<0.05 and sample size (n=109). The study revealed that there is a statistically positive significant relationship between cash flow management and financial performance. Regarding the correlation between working capital management and financial performance was strong, based on (R = .706; sig. <.05). The statistics indicate that a variation working capital management is associated with a strong variation in financial performance. It was concluded that proper financial management practices could enable MFIs to enhance their financial performance. The government and development partners should emphasize on adherence to proper financial management practices in MFIs. Such initiative is expected to enhance MFIs growth and community empowerment. This study recommends that Board of Directors ensures that all assets are registered in the asset register and all Physical Assets that belong to Lyamujungu SACCO be engraved and numbered with clear and visible labels.This study recommends that Management to Lyamujungu SACCO should ensure that expenditure done is in line with the planned budget in order to meet its expectations as far as financial performance is concerned. This study recommends that the Board of Directors need to encourage members to put much money in share capital since it is through this that members can earn a lot of interest and increase on their shares and profits after sharing of dividends. In addition to this some incentives should be given to the members with a good number of shares such as life schemes, to the most saving clients commissions, some token and give some small percentage to loan creditors who pay on time.